2017
DOI: 10.1590/0001-3765201720170224
|View full text |Cite
|
Sign up to set email alerts
|

Landslides Zonation Hazard: relation between geological structures and landslides occurrence in hilly tropical regions of Brazil

Abstract: This paper presents a new approach of landslides zonation hazard studies, based on an integrated study of structural data along with geomorphological and external factors, in a hilly regions of Brazil, covered by a tropical humid rain-forest, called Serra do Mar. The Serra do Mar consists of a hilly region along the east coast of Brazil, with high slopes and many geological structures in a gneiss -migmatitic terrain. In contrast to traditional approaches, this method proposes that structural data (foliation, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 4 publications
(6 reference statements)
0
7
0
4
Order By: Relevance
“…Research has also revealed that landslide occurrence can be closely connected to anthropogenic factors (e.g. deforestation, slope undercutting and construction) (Skilodimou et al, 2018;Cui et al 2019;Jin et al 2020), and geological structures (Cerri et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Research has also revealed that landslide occurrence can be closely connected to anthropogenic factors (e.g. deforestation, slope undercutting and construction) (Skilodimou et al, 2018;Cui et al 2019;Jin et al 2020), and geological structures (Cerri et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Com base nas análises dos escorregamentos, observou-se que encostas com direção e direção de inclinação paralelas ou subparalelas às estruturas geológicas (NE-SW e ENE-WSW, principalmente), tornam muito suscetível a ocorrência de escorregamentos (e.g., Cerri et al, 2017). Isso, com a potencialidade de ocorrência de corridas de massa, deve ser considerado, uma vez que escorregamentos são importantes fontes de materiais para as corridas de massa de origem primária e, quando somados aos sedimentos e materiais depositados nos canais de drenagem, são fontes para as corridas de massa de origem secundária.…”
Section: Análise Da Suscetibilidade/potencialidade à Ocorrência De Counclassified
“…Many studies have attempted to understand the dynamics of Serra do Mar landslides (e.g. Furian et al 1999;Seluchi and Chou 2009;Vieira et al 2010;Dias et al 2016;Cerri et al 2017). However, none of them investigated deeply the role of geological discontinuities, even though Serra do Mar presents a notorious structural control (e.g.…”
Section: Introductionmentioning
confidence: 99%